Evaporation and transpiration processes and changes in their proportional relationships in cotton fields under varying degrees of film biodegradation - Zhang, Hao; Wang, Dong; Zhang, Xun; Lv, Zhiyi; Jia, Tao; Liu, Haijun; Wang, Yifan; Lin, Tao; Tang, Qiuxiang (Frontiers in Plant Science, 2025)
IntroductionBiodegradable film (BE) is completely degraded during use, which effectively addresses the pollution caused by residual film in agricultural fields, serving as an environmentally friendly alternative to traditional polyethylene film (PE). However, BE surface degradation and rupture is a dynamic process, and the relationship between the coverage area and soil moisture and evapotranspiration partitioning changes has yet to be quantified.MethodsTherefore, a field experiment was conducted in 2021 and 2022, employing a film recognition method based on supervised classifiers to monitor the BE degradation area. Variations in evaporation and transpiration were determined in cotton fields under PE and BEs at different irrigation depths.ResultsUnder BE, for every 1% increase in film area damage compared to PE, the soil evaporation rate increased by 0.34 mm∺d−1 (R2 = 0.6027, n = 1613, and p = 0.028). The increased soil evaporation under BEs exacerbated the depletion of deep soil moisture. Compared to seedling stage, the soil water content at 60–80 cm depth under BEs decreased by 28.5–42.13% at the boll-opening stage. Increasing the irrigation depth enhanced the soil moisture content by 5.29–15.37%. Changing the irrigation depth promoted canopy development in cotton fields, increasing the leaf area index by 15.26–25.14% and plant transpiration by 10.32–17.86%.DiscussionIncreases in irrigation depth and canopy coverage in cotton fields had similar inhibitory effects on evaporation as film application, mitigating the gradual increase in soil evaporation caused by BE rupture. Therefore, we suggest that irrigation quotas be appropriately increased when using BEs in oasis cotton areas to achieve coverage effects comparable to PEs.